Supply chain strategies : Demand driven and customer focused - Hines, Tony (New York : Routledge, Taylor & Francis Group, 2024)
"Supply Chain Strategies demonstrates how organizations must take strategic decisions in order to manage their supply chains to sustain competitiveness in the global economy. Whereas many textbooks on supply chain management focus on purchasing and operations, this new edition of Tony Hines' text focuses upon the direction-setting and efficient resource-allocation that organizations need to provide in order to satisfy their customers. Overcoming tensions between political, economic, technological, ethical and environmental considerations is shown to be vital to ensure a sensible strategy for managing the supply chain. The third edition of Tony Hines' successful textbook integrates thoroughly updated international cases to demonstrate how strategic thinking and SCM play out in the real world. It contains a host of useful pedagogy to reinforce your learning including learning outcomes for each chapter, discussion questions and a handy glossary. New to this edition are chapters discussing Supply Chain Risk, procurement strategies and Supply Chain Futures. This book is ideal for courses on supply chain management - especially those which require a strategic element"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business logistics; Strategic planning; Operations management; Inventory control